2010
DOI: 10.1007/s11434-010-0144-0
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological analysis of the Beijing 2008 Hand-Foot-Mouth epidemic

Abstract: This paper presents an empirical analysis of the epidemiological data concerning the 18445 HFMD-infected cases in Beijing in 2008. The main findings are as follows. (i) Seasonal variations in incidence were observed, with a peak observed during the summer season, especially in May. Male patients outnumber female patients by 1.57 : 1. (ii) Most cases occurred in children 4 years old or younger. Outperforming Weibull distribution and Gamma distribution as to model fitness when analyzing patient ages, log-normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
33
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 12 publications
6
33
0
1
Order By: Relevance
“…Multiple linear regression analysis identified temperature as a significant risk factor, which was consistent with the findings of several ecological studies (9,10,12,16) and epidemic trends in Beijing (6)(7)(8). Meanwhile, the univariate analysis showed that temperature was not a significant risk factor.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Multiple linear regression analysis identified temperature as a significant risk factor, which was consistent with the findings of several ecological studies (9,10,12,16) and epidemic trends in Beijing (6)(7)(8). Meanwhile, the univariate analysis showed that temperature was not a significant risk factor.…”
Section: Discussionsupporting
confidence: 87%
“…Based on our results from the univariate analysis, linear regression analysis, and logistic regression analysis, class grade (age) was significantly associated with HFMD outbreaks. Previous surveillance data and studies (6)(7)(8) in Beijing also showed that 2-4-year-old children were more prone to acquire HFMD infections than 4-6-year-old children. Because of the lack of circulating antibodies, 0-4-year-old children are most susceptible to HFMD infections (22,23).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The history of Homo sapiens is always closely interrelated with the study of diseases. Whether it be the Black Death in Europe in the fourteenth century or the superbug that recently spread across the globe like wildfire [1,2], scientists have always looked at diseases with great interest [3][4][5][6][7][8][9][10]. In the well-known theoretical SIS model, the population is divided into two disjoint classes, susceptible individuals and infected individuals, for which the percentages at time t are denoted by s(t) and i(t), respectively [11][12][13][14].…”
mentioning
confidence: 99%